IMPLEMENTASI KEBIJAKAN PENYELENGGARAAN SISTEM PELAYANAN DOKUMEN KEPENDUDUKAN DENGAN MENGGUNAKAN LAYANAN APLIKASI ES MAMA (Ekspedisi Melayani Masyarakat) OLEH DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BITUNG - Oktofianus W. Ch. Tumundo; Joyce Jacinta Rares; Welly ., Waworundeng (AGRI-SOSIOEKONOMI, 2021)
This study aims to get answers about why the implementation of the policy of implementing the Population Document Service System using the Es Ma Ma (Community Service Expedition) application has not given the expected results. This research took place at the Office of Population and Civil Registration of Bitung City. This research design uses a qualitative descriptive approach. The types of data used in this study are primary data and secondary data. What is meant by primary data is data obtained in the field through a deep interview process to informants, both key informants and other supporting informants. The secondary data consists of processed data or data that has been officially published obtained from mass media news, documentation and archives of related institutions. The number of informants in this study amounted to 6 informants consisting of the Head of the Population and Civil Registration Office of Bitung City, 2 operators of the ES MAMA Program Manager and involving 3 community members who were managing population document files. The results of the study indicate that the non-achievement of policy targets is caused by firstly the infrastructure of the implementing organization that is not specifically designed to handle this program, secondly the understanding of the implementers that this program service is part of the "ordinary" service, and thirdly the weak intensity of delivery to the community.